Habilidades metafonológicas en niños y niñas de primer grado de primaria de una institución educativa del Callao - Montoya Lara, Marizol (2012)
The intention of this study was to know the performance of the phonological conscience in its different levels in 71 boys and girls that have concluded the first grade of primary education of a public institution of the Callao. The students come from low and medium socioeconomic level. This skill was evaluated applying the Test de habilidades metalingüísticas (THM) of Gómes, Buadés, Valera and Pérez (1995) adapted in Peru by Rodríguez (2003). The results indicate that 52% of the students are located in the intermediate and low levels. A rigorous analysis between the sub test of the (THM) threw that the metaphonological performances were better in the levels of syllables and of counted phonemes opposite to other dimensions what would explain the difficulties of learning in the reading and writing. Likewise, no significant differences between metalinguistic abilities of children of primary school.